San Francisco Federal Building : San Francisco, California (s.l. : GSA, 2007)
Architect : Mayne, Thom ; Artists : Turrell, James ; Ruscha, Edward ; Garcia, Rupert ; Liu, Hung ; Saunders, Raymond ; Wiley, William T.
boek